Hope amidst despair HIV/AIDS-affected children in Sub-Saharan Africa - Grannis, Susanna W (London Pluto Press, 2011)
"Of the 16 million children to have been orphaned by AIDS worldwide, almost 15 million live in sub-Saharan Africa. Hope Amidst Despair focuses on these children and those who are made vulnerable by HIV/AIDS. Of the millions affected, many live in deep poverty, experience little schooling, have unmet health and psychological issues, and bear the burden of stigma. Their plight is often ignored and, as a result, they lead lives of isolation and exclusion that threaten their futures. The book gives voice to HIV/AIDS orphans, allowing them to tell their stories and explain the challenges they face. Susanna Grannis, founder of CHABHA (Children Affected by HIV/AIDS), shows through first-hand experience and research how young community leaders can, with help, effectively promote children's wellbeing and independence. Readers learn of the complexities and possibilities involved in positive development through the analysis of data on children from five different focus countries of sub-Saharan Africa"--Back cover.
Includes bibliographical references (p. 163-179) and index.
Keywords: AIDS (Disease) in children -- Africa, Sub-Saharan.; AIDS (Disease) -- Africa, Sub-Saharan.; Acquired Immunodeficiency Syndrome -- epidemiology -- Africa South of the Sahara; Child -- Africa South of the Sahara; Acquired Immunodeficiency Syndrome -- prevention & control -- Africa South of the Sahara; Socioeconomic Factors -- Africa South of the Sahara